1999
DOI: 10.1590/s0100-879x1999001200015
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of diethylpropion and alcohol on locomotor activity of mice: participation of the dopaminergic and opioid systems

Abstract: The widespread consumption of anorectics and combined anorectic + alcohol misuse are problems in Brazil. In order to better understand the interactive effects of ethanol (EtOH) and diethylpropion (DEP) we examined the locomotion-activating effects of these drugs given alone or in combination in mice. We also determined whether this response was affected by dopamine (DA) or opioid receptor antagonists. A total of 160 male Swiss mice weighing approximately 30 g were divided into groups of 8 animals per group. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
10
2
Order By: Relevance
“…Two independent reports have found that naloxone (Camarini et al 2001) and naltrexone (Pastor et al 2005) attenuated ethanol-induced locomotor stimulation in outbred Swiss mice. However, Gevaerd et al (1999) and the current study failed to find a significant effect of naloxone pretreatment in Swiss mice. Although these differences could reflect differences in procedure or apparatus, they could also reflect genetic differences in mechanisms associated with ethanol-induced stimulation.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Two independent reports have found that naloxone (Camarini et al 2001) and naltrexone (Pastor et al 2005) attenuated ethanol-induced locomotor stimulation in outbred Swiss mice. However, Gevaerd et al (1999) and the current study failed to find a significant effect of naloxone pretreatment in Swiss mice. Although these differences could reflect differences in procedure or apparatus, they could also reflect genetic differences in mechanisms associated with ethanol-induced stimulation.…”
Section: Discussioncontrasting
confidence: 85%
“…Ethanol induced a significant increase in locomotor activity that was not attenuated by opioid receptor blockade. In another study, naloxone failed to alter the stimulant response of a low dose of ethanol (1.2 g/kg) during a 20-min test in Swiss mice (Gevaerd et al 1999). The mixed results could be associated with differences in testing procedures or with differences in the genotype of mice used in the various experiments.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations